Recommended rejection of the names Malacoplasma gen. nov., Mesomycoplasma gen. nov., Metamycoplasma gen. nov., Metamycoplasmataceae fam. nov., Mycoplasmoidaceae fam. nov., Mycoplasmoidales ord. nov., Mycoplasmoides gen. nov., Mycoplasmopsis gen. nov. [Gupta, Sawnani, Adeolu, Alnajar and Oren 2018] and all proposed species comb. nov. placed therein. Issue 11 (6th August 2019) - Balish, Mitchell; Bertaccini, Assunta; Blanchard, Alain; Brown, Daniel; Browning, Glenn; Chalker, Victoria; Frey, Joachim; Gasparich, Gail; Hoelzle, Ludwig; Knight, Tom; Knox, Christine; Kuo, Chih-Horng; et al.
Abstract : The consensus of the members of the International Committee on Systematics of Prokaryotes' Subcommittee on the taxonomy of Mollicutes is that recently proposed sweeping changes to nomenclature of members of the Mycoplasmatales, specifically involving introduction of the names Malacoplasma gen. nov., Mesomycoplasma gen. nov., Metamycoplasma gen. nov., Metamycoplasmataceae fam. nov., Mycoplasmoidaceae fam. nov., Mycoplasmoidales ord. nov., Mycoplasmoides gen. nov., Mycoplasmopsis gen. nov., and all proposed species or subspecies comb. nov. placed therein, should be rejected because they violate one or more essential points of the International Code of Nomenclature of Prokaryotes.